PARNASIANISM LITERATURE: PHILOSOPHICAL PRINCIPLES, MODELS AND FIGURES OF PARNASIANISM - dika frantiko; Laily Fitriani; Abdurrahman Abror (Journal of Arabic Literature (JaLi), 2023)
Parnasianism is a genre that emerged as a result of its rejection of the Romantic genre. While romanticism exaggerates the subjectivity and emotions, parnasianism genre promotes its inverse. It highlights 'the literature for the literature itself’ which means breaking away from moral and social goals. Through literature study, this study aims to reveal from the historical point of view the emergence of the Parnasianism genre, the forms and models of works, figures, and critics of the Parnasian genre. The result of this study reveals that parnasianism emerged in the mid-nineteenth century as a form of rejection of the romanticism genre since it was too subjective. Thus, this genre emerged with the theme of objectivity towards literary works. The figures in this genre include Leconte de Wisle, Charles Baudelaire, Mala Raimah, Ghautah, Bodler, Benjamin, Kofstan, Victor Kuzan, Ghustav Flaubert, and Thufail. The figures that critic this genre are Walid Qassab, as well as the poet and the writer of Sidney.